Platelet Functions in Relation to Dietary Fats in Farmers from two Regions of France - Renaud, S; Dumont, E; Godsey, F; Suplisson, A; Thevenon, C (Thrombosis and Haemostasis, 1978)
To determine whether the long-term feeding of dietary fats affect platelet functions in man, platelet aggregation (to thrombin ADP, collagen, epinephrine) and clotting activity of platelet-rich plasma (PRP), platelet-poor plasma and of washed platelets, were studied in a mobile-laboratory in 44 healthy male farmers (40-45 years) from two French regions Var and Moselle, in relation to lipemia, glycemia, dietary nutriments, and platelet phospholipid composition. In the Moselle subjects, the platelet clotting activity of PRP and of washed platelets, the platelet aggregation to thrombin and ADP, were highly significantly (p <0.001) increased as compared to those of Var, but not the plasma cholesterol, which was identical in the two regions.In Moselle, the intake of total calories, total lipids and saturated fats was higher than in the Var.However, it was only with the saturated fat intake (mostly stearic acid) that the platelet clotting activity (p <0.01) and the platelet aggregation (p <0.001) were highly significantly correlated. The platelet clotting activity was also significantly (p <0.001) correlated with the fatty acid composition of the platelet phospholipid fractions phosphatidyl serine + phosphatidyl inositol.